Management of gait impairments in people with Charcot-Marie-Tooth disease: A treatment algorithm - Jorik Nonnekes; Cheriel Hofstad; Annemieke de Greef-Rotteveel; Heleen van der Wielen; Janke H. van Gelder; Christian Plaats; Viola Altmann; Fabian Krause; Noël Keijsers; Alexander Geurts; Jan Willem K. Louwerens (Medical Journals Sweden, 2021)
Gait impairments in people with Charcot Marie Tooths disease are the combined result of ankle-foot deformities, muscle weakness, and somatosensory impairments. People with Charcot-Marie-Tooth disease often experience pain and difficulties when walking, especially barefoot. They also trip and fall frequently and have a lower than normal gait speed and distance. Because these gait impairments and related complaints are disabling, clinical management aimed at improving gait is important. Management involves both conservative and surgical treatment options, each with limited scientific evidence. However, a treatment algorithm that describes both conservative and surgical treatment options is currently lacking. This study sets out a step-wise treatment algorithm, based on evidence, if available, and otherwise reflecting practice-based experience. The treatment algorithm will be of value in daily clinical practice, and will serve as a template for future research.